Ovulation rate and its relationship with follicle diameter and gene expression of the LH receptor (LHR) in Nelore cows - Simoes, Renato A. L. [UNESP]; Satrapa, Rafael A. [UNESP]; Rosa, Fernando S. [UNESP]; Piagentini, Marcelo [UNESP]; Castilho, Anthony C. S. [UNESP]; Ereno, Ronaldo Luiz [UNESP]; Trinca, Luzia A. [UNESP]; Nogueira, Marcelo Fábio Gouveia [UNESP]; Buratini, Jose [UNESP]; Barros, Ciro M. [UNESP] (Elsevier B.V., 2012)
The objective was to determine the relationship among the diameter of ovarian follicles, ovulation rate, and gene expression of the LH receptor (LHR) in Nelore cattle. In Experiment 1, ovulation was synchronized in 53 Nelore cows. Three days after ovulation, ovaries were assessed with ultrasonography, all cows were given 6.25 mg LH im, and they were allocated into three groups, according to diameter of their largest ovarian follicle: G1 (7.0-8.0 mm); G2 (8.1-9.0 mm); and G3 (9.1-10.0 mm). For these three groups, ovulation rates were 9, 36, and 90%, respectively, (P < 0.03; each rate differed significantly from the other two). In Experiment 2, granulosa and theca cells were subjected to total RNA extraction, and gene expression of the LHR was determined by RT-PCR. Follicles were allocated in three groups based on their diameter (similar to the Experiment 1), which were denoted Groups A, B, and C. Expression of the LHR gene in granulosa cells was lower in Group A than Group C (P < 0.05). However, there were no significant differences among groups in expression of the LHR gene in theca cells. We concluded that ovulatory capacity in Nelore cattle was related to increased follicular diameter and expression of the LHR gene in granulosa cells. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Follicle; Gene expression; LH receptor; Ovulation; Cattle